METHODOLOGY OF RATING ASSESSMENT OF BUSINESS ENTITIES IN METALLURGY ACCORDING TO NETWORK CHARACTERISTICS - Abdullaeva Matluba Nematovna (Journal of new century innovations, 2023)
Abstract. In this article, the rating evaluation methodology of business entities in metallurgy is considered.